Development betrayed : the end of progress and a coevolutionary revisioning of the future - Norgaard, Richard B., 1943- (Routledge, 1994)
Modernity promised control over nature through science, material abundance through technology and effective government through rational, social organization. Instead of leading to this promised land it has brought us to the brink of environmental and cultural disaster. Why has there been this gap between modernity's aspirations and its achievements? Development Betrayed offers a powerful answer to this question. Development with its unshakeable commitment to the idea of progress, is rooted in modernism and has been betrayed by each of its major tenets. Attempts to control nature h.